2017
DOI: 10.1097/01.aog.0000514941.10478.7c
|View full text |Cite
|
Sign up to set email alerts
|

Modern Learning: How Today’s Obstetrics and Gynecology Residents Gain Knowledge [2I]

Abstract: INTRODUCTION: Little is known about OB-GYN residents’ habits or preferences with regard to self-education. We investigated current resident learning behaviors and preferences, as well as attitudes towards podcasting as an educational tool. METHODS: A 28 question survey was generated to query resident self-education generally and genetics education specifically. An invitation to complete the online survey was sent to all ACGME Program Directors, asking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We assessed 161 full-text articles for eligibility and excluded 99 (see Figure 1). A total of 62 articles met inclusion criteria, 2,3,5,6,13–70 the earliest of which was published in 2007. 52 A summary of the outcomes of each of the included articles is available in Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B218.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We assessed 161 full-text articles for eligibility and excluded 99 (see Figure 1). A total of 62 articles met inclusion criteria, 2,3,5,6,13–70 the earliest of which was published in 2007. 52 A summary of the outcomes of each of the included articles is available in Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B218.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of included studies (n = 44) described the use, availability, and accessibility of podcasts (e.g., number of residents who listen to podcasts, incorporation into medical curricula, ideal podcast length). 2,3,5,6,13,16,17,19,22,24,25,27,29–31,33–36,38–41,43–45,48–50,52–62,65,66,68,69 Many included studies (n = 38) assessed educational outcomes (e.g., learner reactions, knowledge retention, behavior change). 3,6,13-15,17,18,20,21,23-26,28,32,33,36-38,40-42,44-48,51,53,54,57,60,63-65,67,68,70 Some studies reported only descriptive outcomes (n = 24), 2,5,16,19,22,27,29–31,34,35,39,43,49,50,52,55,56,58,59,61,62,66,69 or only educational outcomes (n = 18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations